Institutional choice in social dilemmas: An experimental approach - Ivo Bischoff (Justus-Liebig-Universität Gießen, Fachbereich Wirtschaftswissenschaften, 2002)
This paper presents an experimental study on the ability of human groups to escape the tragedy of the commons through institutional change. It shows that the groups identify institutional change as a means of resolving social dilemmas and are ready to apply it even if the change requires an unanimous vote. At the same time, the groups who were given the right to change the rules performed poorer on average than the control-groups. This result stands in contradiction to elementary economic reasoning as well as the results of previous experimental studies.
Keywords: C92; D71; D62; Q20; 330; social dilemmas; common pool resource; laboratory experiment; group behavior; institutional choice; Gefangenendilemma; Allmenderessource; Institutioneller Wandel; Gruppenentscheidung; Test; Theorie